Signs in use : an introduction to semiotics - Johansen, Jørgen Dines (Routledge, 2002)
This book cuts across different semiotic schools to introduce six basic concepts which present semiotics as a theory and a set of analytical tools: code, sign, discourse, action, text, and culture.